The Role of Live Streaming Towards Customer Engagement in Online Shopping - Abdul Zaini, Sharmella; Salim, Siti Aisyah (Research in Management of Technology and Business, 2023)
Live streaming is a video broadcast happens in real time and has been used as direct selling tools especially among small businesses. This online tool has become quite popular as it could improve the sales performance as well as build customer engagement. Most past studies have just focus on the relationship between online shopping and customer engagement and there is still a lack of studies that looked into live streaming towards customer engagement in Malaysia context. Thus, this study aims to examine the role of live streaming towards customer engagement in online shopping. The Stimuli- Organisms- Responses (SOR) and Uses and Gratifications Theory (UGT) has been adopted as the theoretical foundation in this research. This study has collected data from 141 respondents of Malaysian online shopping users among Gen Z. Quantitative research has been used in this research, where online surveys has been distributed to Malaysian online shopping users among Gen Z. All the collected data were analyzed using  Statistical Package for Social Science (SPSS). From the analysis, all the variables towards customer engagement show a positive significant relationship towards customer engagement with the correlation coefficient 0.645. This study can provide the importance of live streaming usage towards customer engagement in online shopping and these findings will help future researchers and acquire knowledge through this research.